AJARAN MILLAH IBRAHIM DALAM PANDANGAN MUI KOTA CIREBON (Studi Putusan Fatwa MUI Kota Cirebon Nomor 070/ HF-MUI-KC/XII/2009) - Ridwan Umar; Wasman Wasman (UIN Siber Syekh Nurjati Cirebon, 2019)
Â ABSTRACTThe Millah Abraham community, better known as Komar, is one of the religious groups in Islam that developed in Cirebon City, West Java. This group is considered to deny the Prophet Muhammad and deviate because he cultured Ahmad Mushaddeq as a prophet calling him the Al-Maw'ud based on the book he believed